2018
DOI: 10.7439/ijbr.v9i5.4769
|View full text |Cite
|
Sign up to set email alerts
|

Lassa fever: A recurring decimal in Plateau state, Nigeria

Abstract: Background: Since the first reported case of Lassa fever (LF) in Jos, Plateau state Nigeria in the early 70's, the state has been plagued with increasing number of cases. This could be due to poor environmental practices, food and personal hygiene. By the end of August 2017 there were 42 reported cases with 15 confirmed cases. Sadly, over the years there have been challenges with reporting and investigation of cases. This could be due to weak health systems commonly seen in developing countries. Methods and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is also interesting to note that two local governments constituted 50% of cases; urban underprivileged communities of Jos North and rural settlements of Langtang North LGA. Previous studies in Plateau State had indicated a higher burden of LF in Jos North LGA [19,20]. Recent studies suggest that 80% of outbreaks are largely fuelled by independent zoonotic transmission events from infected rodent hosts [21].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…It is also interesting to note that two local governments constituted 50% of cases; urban underprivileged communities of Jos North and rural settlements of Langtang North LGA. Previous studies in Plateau State had indicated a higher burden of LF in Jos North LGA [19,20]. Recent studies suggest that 80% of outbreaks are largely fuelled by independent zoonotic transmission events from infected rodent hosts [21].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Other studies have similarly shown that over the years there has been an increase in the number of reported cases. Between 2012 and 2016, a study carried out in Plateau state showed that there was a steady rise in the number of observed LF cases, although that of 2015 was lower than the preceding year [20]. A study carried out in Irrua specialist Hospital, Nigeria also showed increasing caseload of LF from 2015 to 2018 [21].…”
Section: Discussionmentioning
confidence: 99%